Approach Transformational Leadership: Organizational Goal & Employee Retention - Wenny Desty Febrian; Rubadi Rubadi; Didin Sjarifudin; Andi Muhammad Sabilillah Tahir; Erni Perwitasari (ABNUS Publisher, 2023)
This scientific article provides a view of the elaboration of scientific article literature that supports existing variables. The method used is qualitative using graphic techniques, by searching literature in the form of articles related to the variables in this article, which come from sources of international journals, the internet, and books.Â After that, it is described from the results of the objectives and findings or results into a form of reinforcement for this article with the findings of the article literature. As a result of organizing effective organizational goals, empowering employees, and creating a constructive work environment, transformational leaders are able to motivate employees to achieve outstanding performance. In addition, transformational leaders who create a work climate that enables employee development and pays attention to their needs also contribute to long-term employee retention. This article adds a qualitative view of the existing variables, so as to provide references for other researchers, as well as the results of contributing to science and knowledge in the field of human resources.